The Association between Gender, Personal Hygiene Indicators, and Occupancy Density with the Incidence of Pediculosis Capitis at Madrasah Tsanawiyah Pondok Pesantren (Ponpes) Nurus Sunnah Semarang - Mashuri, Yusuf Ari; Gandari, Hijriyah Putri; Yulia Sari (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2024)
Background: Pediculosis capitis is one of the neglected tropical diseases (NTDs) caused by Pediculus humanus capitis, an obligate ectoparasite that lives parasitically on human skin. This disease is most common in women, in people with poor personal hygiene, and in densely populated areas. Boarding schools are densely populated and pose a risk for transmission of pediculosis capitis due to the many interactions among residents. Purpose: This study aims to investigate the association between gender, personal hygiene indicators, and occupancy density with the incidence of pediculosis capitis at Madrasah Tsanawiyah Pondok Pesantren Nurus Sunnah Semarang. Methods: In this cross-sectional observational study, all the junior high school students at Ponpes Nurus Sunnah were included in a total of 49 subjects. The data were collected by filling out questionnaires, doing a direct examination of the hair, and counting the measurements of the room area. Data analysis was performed using SPSS 23.0 for Windows. Result: Pediculosis capitis infestation was found among 13 (26.5%) students, with a higher incidence in females (46.4%) than males (0%), in respondents with the habit of combing hair using a personal comb (37.1%), and in non-densely populated areas (58.8%). There was an association between gender (p=0.000), the habit of combing hair using a personal comb (p=0.006), and occupancy density (p=0.000) and the incidence of pediculosis capitis. Conclusion: Gender, the habit of combing hair using a personal comb, and occupancy density are associated with the incidence of pediculosis capitis...